Job performance and chemical dependency : a practical guide for managers and supervisors - Voorhees, Lynda A. (Crisp Pub. Menlo ParkUS, 1992)
Provides information, case studies and exercises to help supervisors understand substance abuse and learn how to deal with it in the workplace. Lists some signs of chemical dependency in employees.